Historiography of Educational Institutions in Aceh before Independence - Ismail Muhammad; Safrina Ariani; Aisyah Idris (the Faculty of Education and Teacher Training of the Institut Agama Islam Negeri (IAIN) Langsa, 2025)
Aceh has a complex history that is often obscured by its social and political contexts, encompassing both evolutionary and revolutionary aspects. The historiography of education in Aceh, especially during the pre-independence period, is inadequately explored and lacks a comprehensive investigation. The younger generation of Aceh exhibits a restricted understanding of the educational history of their region. This study examines the historical context of pre-independence educational institutions in Aceh, focusing on the institutions and their developmental trajectories. The study employed qualitative methodology utilising library research. The study's findings are presented as follows: Dayah represents the earliest educational institution in Aceh, originating from the Islamic Kingdom of Peureulak, specifically Dayah Cot Kala, in the third Hijri century, or the early 9th century. It served as an institution that educated the community in Islamic beliefs and enabled their effective practice. The first Dutch educational institution founded in Aceh was the Tweede Klasse School (Second Class School) in 1907. Subsequent educational institutions that emerged included the Europese Lagere School (ELS), Eerste Klasse School, Volksschool, Hollands Inlandse School (HIS), and Meer Uitgebreid Lager Onderwijs (MULO). The Dutch educational system in Aceh was implemented to mould society in alignment with the three aims of colonisation: glory (victory and power), gold (wealth and riches), and gospel (Christianization efforts). The Dutch educational system aimed to cultivate office and field workers who adhered to national standards. During the Japanese occupation, education in Aceh underwent minimal changes, primarily limited to the renaming of schools to align with Japanese nomenclature. Japan mandates the study of the Japanese language, respect for Japanese culture, and kinrohoshi (mutual assistance). Madrasah al-Khairiyah, the first madrasah, was founded in Aceh in 1916 AD by Teungku Muhammad Saman Siron, located near the Baiturrahman Grand Mosque in Kuta Raja. This institution exemplified the modernisation of dayah education by integrating non-Islamic subjects, including Arithmetic, Geography, and History. As a result, Islamic education is characterised by a non-dichotomous nature